Gezici mevsimlik tarım işçilerinin 36-72 aylık çocuklarına yönelik geliştirilen aile eğitim programının ve okul öncesi eğitim etkinliklerinin etkilerinin incelenmesi - Azaklı, Tuğba Kontaş (My University, 2021)
Gezici mevsimlik tarım işçisi aileler yıl içinde birden fazla şehre giderek, tarım alanında zorlayıcı koşullarda göçe kona yaşamaktadırlar. Çocuklar da bu göç yolu boyunca ailelerine eşlik etmektedir. Karmaşık bir olgu olan mevsimlik tarım göçü, yola çıkan her bireyi etkilese de elbette en çok etkilenenler en kırılgan durumda olan çocuklardır. Bu araştırmanın amacı gezici mevsimlik tarım işçisi ailelere ve 36-72 aylık çocuklarına uygulanacak aile eğitim okul öncesi eğitim etkinliklerinin annelerin ebeveynlik becerilerine ve çocukların gelişim düzeylerine etkisinin incelenmesidir. Bu araştırmada eş zamanlı ve eşit statülü karma yöntem deseni kullanılmıştır. Araştırmanın nicel kısmında deney ve kontrol gruplu ön test son test deseni kullanılmış olup, nitel kısmında ise durum çalışması yöntemi kullanılmıştır. Bu araştırmanın evrenini 2019 fındık hasadı döneminde 36-72 ay arası çocuğu ile İkizce ilçesine gelerek mevsimlik tarım işinde çalışan anneler ve çocuklar oluşturmaktadır. Örneklem ise çalışmaya katılmaya gönüllü 15 anne ve 17 (üçü kardeş) çocuktan oluşmaktadır. Çalışmanın başında araştırmaya katılmayı kabul eden katılımcılar arasından çocuklarını yaz okuluna gönderen ve kendileri de aile eğitimine katılmayı kabul eden beş anne ve beş çocuk Deney 1 Grubu’nda yer almıştır. Çocuklarını yaz okuluna gönderen ancak aile eğitimine katılmak istemeyen beş anne ve yedi çocuk (üçü kardeş) Deney 2 Grubu’nda yer almıştır. Çocuklarını yaz okuluna göndermeyen ve kendisi de aile eğitimine katılmak istemeyen ancak araştırmaya katılmayı kabul eden beş anne ve beş çocuk ise Kontrol Grubu’nda yer almıştır. Araştırma kapsamında okul öncesi çağda çocuğu olan gezici mevsimlik tarım işçilerinin mevcut koşullarına ve kültürlerine duyarlı bir aile eğitim geliştirilmiştir. Gezici mevsimlik tarım işçilerinin çocuklarına yönelik ise okul öncesi eğitim programına bağlı kalınarak okul öncesi eğitim etkinliklerinden oluşan bir paket destek hazırlanmıştır. Ayrıca araştırmada kültüre duyarlı bir Mevsimlik Göç Eden Aile ve Çocuklara Yönelik Senaryo Temelli Değerlendirme Aracı geliştirilmiştir. Araştırma sonunda oldukça kısa süreli olan (beş haftalık) aile eğitimi müdahalesinin annelerin bilgi, beceri ve yaklaşımlarında olumlu anlamda kalıcı değişiklik yaratarak etkili olduğu; beş haftalık okul öncesi eğitim etkinlikleri müdahalesinin ise çocukların psikomotor, bilişsel, dil ve sosyal duygusal gelişim alanlarında olumlu anlamda kalıcı değişiklik yaratarak etkili olduğu belirlenmiştir. Hem anneleri hem de kendileri müdahale grubunda yer alan Deney 1 Grubu’ndaki çocukların diğer gruplardaki çocuklara göre daha yüksek oranda ve kalıcı bir sosyal duygusal gelişim gösterdikleri belirlenmiştir. Annelere ve çocuklara birlikte eğitim uygulamanın daha etkili olduğu bu çalışmanın en önemli sonucudur.

Mobile seasonal agricultural worker families travel to many cities for temporary jobs throughout the year and live in harsh and challenging conditions. Children have to be with their families during this migration since there is no better alternative for them. Thus, in addition to their work, families have to accomplish one important mission as well which is raising their children under difficult conditions. Although seasonal agricultural migration, which is a complex phenomenon, affects every individual who participates in the migration, of course, those who are most affected are the most vulnerable children. The main purpose of this study is deep examination of the effects of a family education program and preschool education activities on mothers' parenting skills and children's developmental levels to be applied to 36-72 month-old children and mothers of seasonal agricultural worker families. In this study, the simultaneous and equal status mixed method design was used. In the quantitative part of the research, the pre-test post-test design with experimental and control groups was used, while the case study method was used in the qualitative part. The population of this research consists of mothers and children whose mother tongue is Kurdish and who come to İkizce district with their 36-72 month old children during the 2019 hazelnut harvest period and work in seasonal agriculture. The sample consists of 15 mothers and 17 (three siblings) children who volunteered to participate in the study. Among the participants who agreed to participate in the study at the beginning of the study, five mothers and five children who sent their children to summer school and who agreed to participate in family education were included in the Experimental 1 Group. five mothers and seven children (three siblings) who sent their children to summer school but did not want to participate in family education were included in the Experimental Group 2. Five mothers and five children who did’nt send their children to summer school and did’nt want to participate in family education, but agreed to participate in the study, were included in the Control Group. Within the scope of the research, a family education program that is sensitive to the current conditions and cultures of migrant seasonal agricultural workers with pre-school children has been developed. For the children of mobile seasonal agricultural workers, a package support program consisting of pre-school education activities was prepared by adhering to the pre-school education program. In addition, a culture-sensitive Scenario-Based Assessment Tool for Seasonal Migrant Families and Children was developed in the research. At the end of the research, it was determined that the family education intervention, which is very short (five weeks), was effective by creating a positive and permanent change in the knowledge, skills and approaches of the mothers; It was determined that the intervention of five week preschool education activities was effective by creating positive and permanent changes in the psychomotor, cognitive, language and social-emotional development areas of children. It was determined that the children in the Experimental Group 1, whose mothers and themselves were in the intervention group, showed a higher rate of permanent social-emotional development than the children in the other groups. The most important result of this study is that applying education to mothers and children together is more effective.Mobile seasonal agricultural worker families travel to many cities for temporary jobs throughout the year and live in harsh and challenging conditions. Children have to be with their families during this migration since there is no better alternative for them. Thus, in addition to their work, families have to accomplish one important mission as well which is raising their children under difficult conditions. Although seasonal agricultural migration, which is a complex phenomenon, affects every individual who participates in the migration, of course, those who are most affected are the most vulnerable children. The main purpose of this study is deep examination of the effects of a family education program and preschool education activities on mothers' parenting skills and children's developmental levels to be applied to 36-72 month-old children and mothers of seasonal agricultural worker families. In this study, the simultaneous and equal status mixed method design was used. In the quantitative part of the research, the pre-test post-test design with experimental and control groups was used, while the case study method was used in the qualitative part. The population of this research consists of mothers and children whose mother tongue is Kurdish and who come to İkizce district with their 36-72 month old children during the 2019 hazelnut harvest period and work in seasonal agriculture. The sample consists of 15 mothers and 17 (three siblings) children who volunteered to participate in the study. Among the participants who agreed to participate in the study at the beginning of the study, five mothers and five children who sent their children to summer school and who agreed to participate in family education were included in the Experimental 1 Group. five mothers and seven children (three siblings) who sent their children to summer school but did not want to participate in family education were included in the Experimental Group 2. Five mothers and five children who did’nt send their children to summer school and did’nt want to participate in family education, but agreed to participate in the study, were included in the Control Group. Within the scope of the research, a family education program that is sensitive to the current conditions and cultures of migrant seasonal agricultural workers with pre-school children has been developed. For the children of mobile seasonal agricultural workers, a package support program consisting of pre-school education activities was prepared by adhering to the pre-school education program. In addition, a culture-sensitive Scenario-Based Assessment Tool for Seasonal Migrant Families and Children was developed in the research. At the end of the research, it was determined that the family education intervention, which is very short (five weeks), was effective by creating a positive and permanent change in the knowledge, skills and approaches of the mothers; It was determined that the intervention of five week preschool education activities was effective by creating positive and permanent changes in the psychomotor, cognitive, language and social-emotional development areas of children. It was determined that the children in the Experimental Group 1, whose mothers and themselves were in the intervention group, showed a higher rate of permanent social-emotional development than the children in the other groups. The most important result of this study is that applying education to mothers and children together is more effective.
Investigation of the effects of the family education program and pre-school education activities for the 36-72-months children of migrant seasonal agricultural workers
Keywords: 36-72 Aylık Çocuklar; 36-72 Months-Old Children; Agricultural laborers; Aile eğitimi; Early Intervention; Erken Müdahale Preschool education; Family education; Gezici Mevsimlik Tarım İşçileri; Migrant Seasonal Agricultural Workers; Okul öncesi çocuklar; Okul öncesi eğitim; Okul öncesi öğretim; Preschool children; Preschool teaching; Tarım işçileri